Penerapan dan Pengaruh Pendidikan Agama Islam Pada Masa Pandemi - Aminuddin Aminuddin (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2020)
Islamic religious education is education that must be maintained by Muslims throughout their lives for Muslims to learn from generation to generation. it is so important that this education is learned and developed. Islamic religious education brought by the Prophet Muhammad SAW, is the teachings of Rahmatanlil'alamin, for Muslims that we must learn. Pendiaka Islam teaches us to live cleanly, we can divide it into two, first clean birth, second clean mind, clean birth, namely clean limbs of clothing and the place where we are. Teachers today are the basic foundation for children's lives to achieve complete educational progress. Education in this New Normal era requires a lot of things that are demanded by people, teachers and students, where all stakeholders are required to be able to solve problems that exist in related institutions. This booklet invites how to deal with learning in the new normal era, such as with media zoom meetings, goegle classromm, goegle form etc